Uso De Las Tecnologías De La Información Y Comunicación Y El Aprendizaje Logrado Por Los Estudiantes Del Centro De Educación Básica Ciudad De Ventanas, En El Cantón Ventanas, Provincia De Los Ríos. - Pasto Toapanta Irma Angélica (2015)
Information technology to be the set of techniques, procedures and electronic devices for data processing, they have become a new concept for students and teachers, contributing to the significant learning, so the purpose of the research was determine the extent to classroom availability of these technologies affect the teaching-learning process, being a transverse current reality in educational institutions of the country, since the technology is no stranger to the educational process, by the fact that students prefer to use compared to traditional classes, but in educational institutions teachers are not updated to how to integrate effectively in the learning process, Silvering iinvestigar the aim of the relationship between the use of information technology and communication for student learning, justified by the fact that these technologies are important in learning to align main element receiving and disseminating student information, so their influence in the education system is necessary for teachers to develop their classes. For this descriptive research methodology, country, documentary, applied, in qualitative method was used. Techniques for collecting information were observation and survey, surveys teachers, students and parents were conducted, the results were analyzed and processed by means of tables and graphs, allowing an orderly representation, concluding that the information technology and media influence for the benefit of student learning, motivating teaching resource as due to the interest of students by computer tools and multimedia interactive programs, which can be exploited in the process of learning, raising the educational improvement proposal through strategies for improving the use of information technology and communication, aimed at teachers and students.